2021
DOI: 10.1029/2021jb022354
|View full text |Cite
|
Sign up to set email alerts
|

Mantle Flow in the Vicinity of the Eastern Edge of the Pacific‐Yakutat Slab: Constraints From Shear Wave Splitting Analyses

Abstract: To investigate the effects of a slab edge and varying slab geometry on the mantle flow systems beneath south central Alaska, a total of 971 pairs of teleseismic shear wave (SKS, SKKS, and PKS) and 65 pairs of local S wave splitting parameters (fast orientations and splitting times) are measured using data from the USArray and other networks. The Pacific‐Yakutat slab edge separates two regions with different characteristics of the splitting measurements. The area to the west of the slab edge has greater splitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Abaga volcanic field, one of the largest intraplate volcanic areas in the late Cenozoic in eastern Asia, has complex geological structures and ambiguous geodynamic causes (Xu et al, 2019;Zhang & Guo, 2016). It has been shown that events from different back-azimuth directions have the 10.1029/2021GL097116 of 11 possibility of identifying "piercing point dependent" anisotropy, as recently highlighted by several shear wave splitting studies in Alaska (Yang et al, 2021), Sichuan Basin (Jia et al, 2021) and Central Myanmar areas (Fan et al, 2021). Therefore, it must be mentioned that the existence of complex anisotropy around this intraplate volcano cannot be entirely ruled out and it could be left for future detailed investigation.…”
Section: West Of the Nsgl -Lithospheric Deformation Related Anisotropymentioning
confidence: 99%
“…Abaga volcanic field, one of the largest intraplate volcanic areas in the late Cenozoic in eastern Asia, has complex geological structures and ambiguous geodynamic causes (Xu et al, 2019;Zhang & Guo, 2016). It has been shown that events from different back-azimuth directions have the 10.1029/2021GL097116 of 11 possibility of identifying "piercing point dependent" anisotropy, as recently highlighted by several shear wave splitting studies in Alaska (Yang et al, 2021), Sichuan Basin (Jia et al, 2021) and Central Myanmar areas (Fan et al, 2021). Therefore, it must be mentioned that the existence of complex anisotropy around this intraplate volcano cannot be entirely ruled out and it could be left for future detailed investigation.…”
Section: West Of the Nsgl -Lithospheric Deformation Related Anisotropymentioning
confidence: 99%
“… (a) Comparison of human‐determined (blue bars; Yang et al., 2021) and convolutional neural network (CNN)‐selected (red bars) shear wave splitting measurements in south central Alaska. Green bars are measurements accepted by both CNN and human operators.…”
Section: Discussionmentioning
confidence: 99%
“…We next apply the trained CNN to broadband seismic data in south central Alaska recorded by 127 stations with variable recording period from 1988 to October 2019. The procedures to request (from the Data Management Center of the Incorporated Research Institutions for Seismology) and preprocess the XKS data follow those described in Liu and Gao (2013) and are identical to those used by Yang et al (2021). In total 19,960 pairs of splitting parameters are obtained at 127 Stations (Figure 3a).…”
Section: Application To Sws Measurements In South Central Alaskamentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies using shear wave splitting (SWS, a tool that the current study employs) have demonstrated that trench retreat and the accompanying slab rollback can induce trench‐parallel entrained mantle flow in the subslab region and trench‐normal corner flow in the mantle wedge above the slab (e.g., Becker & Faccenna, 2009; Long & Becker, 2010; Schellart, 2004; Sternai et al., 2014). In addition, driven by the difference of pressure across the subducted slab, part of mantle flow in the subslab may enter the mantle wedge through lateral slab edges or slab windows (e.g., Faccenda & Capitanio, 2013; Fan et al., 2021; Yang et al., 2021). The horizontal component of the various flow systems could be readily characterized and constrained by the strength and orientation of seismic azimuthal anisotropy (Silver & Chan, 1991; Zhang & Karato, 1995).…”
Section: Introductionmentioning
confidence: 99%